2006
DOI: 10.1042/cs20050342
|View full text |Cite
|
Sign up to set email alerts
|

Current status of pancreatic islet transplantation

Abstract: DM (diabetes mellitus) is a metabolic disorder of either absolute or relative insulin deficiency. Optimized insulin injections remain the mainstay life-sustaining therapy for patients with T1DM (Type I DM) in 2006; however, a small subset of patients with T1DM (approx. 10%) are exquisitely sensitive to insulin and lack counter-regulatory measures, putting them at higher risk of neuroglycopenia. One alternative strategy to injected insulin therapy is pancreatic islet transplantation. Islet transplantation came … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
81
0
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(84 citation statements)
references
References 97 publications
0
81
0
3
Order By: Relevance
“…1,15 However, the procedures during the isolation process may cause cellular dysfunction. It has been previously reported that oxidative stress plays a major role in triggering the death of islets.…”
Section: Discussionmentioning
confidence: 99%
“…1,15 However, the procedures during the isolation process may cause cellular dysfunction. It has been previously reported that oxidative stress plays a major role in triggering the death of islets.…”
Section: Discussionmentioning
confidence: 99%
“…Os primeiros sucessos em aloenxertos de ilhotas no tratamento cirúrgico de diabetes ocorreram em 1990 com Scharp et al 4 que alcançaram a insulino-independência em um paciente portador de DM1 em um intervalo de um mês. No entanto, muitas dificuldades técnicas foram encontradas para prosseguir no desenvolvimento da reprodução deste experimento.…”
Section: Introductionunclassified
“…Na década de 1991 a 2000, foram realizadas 450 tentativas de transplante de ilhotas em pacientes com DM1, com índice de sucesso de apenas 8%. 50% do sucesso dos casos foram obtidos e reportados, quando os pacientes tinham se tornado diabéticos por terem sido submetidos à pancreatectomia 4 . Até que em 1999/2000, Shapiro et al obtiveram sucesso na independência de insulina em 7 pacientes diabéticos, realizando os experimentos com base no protocolo modificado de Edmonton 7 .…”
Section: Introductionunclassified
“…Effective treatment demands transplant of 8000 to 10 000 islet equivalents per kilogram of patient body weight. 1 The main problem related to islet transplant is shortage of human pancreata. Solutions for deficiency of organs from deceased donors may be cryopreservation of isolated islets, which involves tissue collection and long-term storage.…”
Section: Introductionmentioning
confidence: 99%